THE DEVIATION IN THE IMPLEMENTATION OF LOCAL GOVERNMENT’S PUBLIC POLICIES: PERSPECTIVES FROM PUBLIC INTEREST AND SELF INTEREST - Xinyue Chen (PEOPLE: International Journal of Social Sciences, 2026)
Since the emergence of policy implementation research in the West during the 1970s, it has become a vital area of academic inquiry in public policy and administrative studies. Policy implementation forms the essential link between policy formulation and execution, determining the ultimate success of public governance. In China’s political system, local governments serve as key executors positioned between central directives and local realities. This dual role they adopt not only enhances the flexibility and efficiency of policies through their obedience to the central government and their autonomy in local adaptation, but also provides space for selfishness and rent-seeking behavior, resulting in deviations during the implementation process. The purpose of this study is to analyze the mechanisms and driving factors behind these policy implementation deviations at the local level. Drawing upon interdisciplinary theories of political science, public administration, and policy studies, this research adopts the “policy fuzziness-conflict” framework to investigate the tension between public interest and self-interest within local government behavior. Through theoretical analysis and literature synthesis, the study constructs a comprehensive framework that integrates local government attributes, intergovernmental relations, and administrative functions. Findings reveal that policy ambiguity, interest conflicts, and structural incentives significantly influence deviation behaviors. The conclusion emphasizes the need to strengthen institutional coordination and value alignment to enhance the effectiveness of public policy execution and promote sound local governance in China.